PENGARUH PEMBIAYAAN MUSYARAKAH TERHADAP PROFITABILITAS PADA BANK UMUM SYARIAH (BUS) PERIODE 2015-2017 - Auditya, Lucy; Afridani, Lufika (Institut Agama Islam Bengkulu, 2018)
The purpose of this study was to determine the effect of musyarakah financing on profitability in Sharia Commercial Banks in Indonesia for the 2015-2017 period and to find out how much influence musyarakah financing had on profitability in sharia commercial banks for the period 2015-2017. The limitation of the problem of this research is on the profitability of financial ratios ROA (Return On Assets) and ROE (Return On Equity). To disclose these issues in depth and thoroughly, researchers used a quantitative approach with secondary data collection techniques in the form of financial statements of each sharia bank for three consecutive years and provided quarterly financial reports, obtained by 5 Islamic banks to obtain 60 data. The data analysis technique used is simple linear regression using the SPSS version 16. Then the data is described, analyzed and discussed to answer the problems raised. From the results of the study it was found that musyarakah financing had a significant effect on ROA at alpha 5%. This is evidenced by the significance value (Sig.) (0.002) <(Î±) 0.05. While musyarakah financing has no significant effect on ROE at alpha 5%. This is evidenced by the significance value (Sig.) (0.669)> (Î±) 0.05.